(3cJGH GdcTGas - (3GdnqRnerNnTpQj GdNhGQRej, CHh GdbGSe, LGQ Gddg, eMehO Hf YeQ Hf eMeO Hf CMeO, (B538 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd GdbQBf cdGeG efXeG hfRdg HMSH GdeUGdM efLeG GYde Cf eJf cd Yde hYehO cd UfGYI WHbGJ GdYdeGA ajg eJOGfjIs
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde(B: (3ef bQC ShQI GdYfcHhJ cGf dg ef GdCLQ YTQ MSfGJ HYOO cd GdeDefjf hGdefGabjf Je GdLRA GdChd jJdhg Chd GdLRA GdKGfj ShQI GdQhes
(3ebGHdI HJGQjN(B: (3SfI (B1178(3g`s
(3JHUQI GdYfhGf (B:s
(3JaSjQ GdReNTQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/178s
(3cTa GdXfhf (B2/1475s
Keywords: (3GdJaSjQ hYdhe GdbQBfs